DESAIN SISTEM INFORMASI PERPUSTAKAAN UNIVERSITAS STIKUBANK SEMARANG BERBASIS WEB - Listiyono, Hersatoto; Sani, Diah Laila; Khristianto, Teguh; Soelistijadi, R. (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
Libraries are part of learning resources that must be owned by every school or college. Because students easily find information or knowledge through the library. With the development of technology, people think to be able to work more effectively and efficiently. The purpose of this study is to create an information system to overcome these limitations in order to improve services to library users and expedite the administrative process to be faster and more accurate. The design of a web-based library information system is expected to improve maximum library services and errors in data processing. The library information system includes member registration, search books, book data, borrowing books, books, and fines for late payment of books.